2017
DOI: 10.1186/s13045-016-0370-2
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in cancer: an emerging key player

Abstract: Circular RNAs (circRNAs) are a class of endogendous RNAs that form a covalently closed continuous loop and exist extensively in mammalian cells. Majority of circRNAs are conserved across species and often show tissue/developmental stage-specific expression. CircRNAs were first thought to be the result of splicing error; however, subsequent research shows that circRNAs can function as microRNA (miRNA) sponges and regulate splicing and transcription. Emerging evidence shows that circRNAs possess closely associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
207
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(210 citation statements)
references
References 56 publications
(70 reference statements)
2
207
0
1
Order By: Relevance
“…Similar to lncRNA, circRNAs were mainly used as a miRNA sponge to compete with miRNAs, reversing the inhibitory effect of miRNA downstream genes, thus increasing the expression of target genes [31]. Memczak found that CDR1as had 63 conservative binding sites to miR-7 in nervous tissue.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Similar to lncRNA, circRNAs were mainly used as a miRNA sponge to compete with miRNAs, reversing the inhibitory effect of miRNA downstream genes, thus increasing the expression of target genes [31]. Memczak found that CDR1as had 63 conservative binding sites to miR-7 in nervous tissue.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Recently much attention has been paid to Circular RNAs (circRNAs), which is one of a class of noncoding RNAs, with circular structure by joining the 3′end of the RNA to the 5′end . They were important in regulating the expression of other genes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently much attention has been paid to Circular RNAs (circRNAs), which is one of a class of noncoding RNAs, with circular structure by joining the 3′end of the RNA to the 5′end. 4 They were important in regulating the expression of other genes. For example, Liu et al found 2:27713879|27755789 and 2:240822115| 240867796 participated in regulation network in osteogenic differentiation.…”
mentioning
confidence: 99%
“…The stability of circRNA partly contributes to their abundant expression. It is indicated that the expression level of some circRNAs is higher than that of their corresponding linear mRNAs [42]. Therefore, circRNAs seem to possess distinct advantages as candidate biomarkers for cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%